Secure topology for electronic medical record transmission - Alanazi, Hamdan O.; M.L., Mat Kiah; Zaidan, Bilal Bahaa; Zaidan, A.A.; Alam, Gazi Mahabubul (Science Alert, 2010)
In this study, handshake protocol for patient, medical center and doctor, medical center is proposed for electronic medical record transmission to improve the confidentiality of data transmission and non-repudiation of sending and receiving medical records. The proposed topology depends on symmetric and asymmetric cryptography to achieve high level of secrecy for electronic medical records. The new topology has been described on multi-users (i.e., Doctors and Patient). The new topology has been implemented using Ntru crypto-system and AES encryption method. The proposed solution has been tested to have high level of confidentiality up to the legal age of the medical records.